Investigating social cognition in epilepsy using a naturalistic task. (26th July 2016) - Bujarski, Krzysztof A.; Flashman, Laura; Li, Zhongze; Tosteson, Tor D.; Jobst, Barbara C.; Thadani, Vijay M.; Kobylarz, Erik J.; Roberts, David W.; Roth, Robert M.
Summary: Objective: The primary objective for this study was to assess social cognition in patients with focal epilepsy using a naturalistic task, which accurately models complex real‐world social interaction. Methods: We conducted an observational study of social cognition in 43 patients with focal epilepsy and in 22 controls. Patients and controls completed The Awareness of Social Inference Test, which measures both basic and advanced social cognition in a realistic video‐based format. Patient and controls also completed standard measures of cognitive functioning and measures of depression. Results: Compared to controls, we found that patients with epilepsy (PWEs) had no difficulty identifying positively valenced emotional states (happiness) yet had difficulty identifying most negatively valenced emotional states (anger, fear, and disgust). In addition, PWEs were able to identify sincere exchanges correctly but could not identify sarcastic and insincere exchanges. We found that basic social cognition significantly correlated with standard generalized cognitive measures, whereas advanced social cognition did not. Finally, age at onset had significant impact on social cognition, whereas other epilepsy characteristics did not. Significance: PWEs have deficits in social cognition when measured using a naturalistic video‐based task. Advanced social cognition may be an independent cognitive domain in PWEs that is not adequately measured using standard psychometric instruments. Problems with social cognition may arise as a consequence of epilepsy during the periods of robust social development in childhood and adolescence.